RESISTANCE, ANCESTRY, AND COLLECTIVITY IN INDIGENOUS EDUCATION - Viana Moreira, Áurea; Rocha Leal Araújo, Giovanna; Gomes Lopes, Fernanda (Cadernos ESP, 2026)
This article aims to report the experience of Psychology students in conducting a focus group with teachers and staff from an Indigenous school located in the municipality of Pacatuba, Ceará, seeking to understand the teaching profession and educational practices in this context. This is a qualitative study, structured as an experience report, carried out within an internship course, using participant observation, semi-structured interviews, and a focus group as research techniques. The results showed that the Indigenous school functions as a space of cultural resistance, in which education is intrinsically connected to ancestry, spirituality, and collectivity. The observed pedagogical practices go beyond the hegemonic school model, valuing intergenerational knowledge transmission and collective work. It is concluded that the experience contributed to the appreciation of Indigenous knowledge and to strengthening the students’ academic training, reaffirming the importance of research practices committed to the decolonization of knowledge.